A INFLUÊNCIA DA LIDERANÇA COMO ESTÍMULO À MOTIVAÇÃO DE EQUIPES VIRTUAIS - Silva, Rovílson Dias da (2007)
There is great interest in the optimization of the efficiency of the work force. One of the major aspects is the availability of new technology, and how it interacts with the work force. The leadership has always been considered an essential feature of the administration process, however, how does it develop in virtual teams is not fully understood. Here we present some results on an investigation of the role of the leadership on the behaviour of the virtual teams. Ten subjects from a French company located in Sao Paulo region who work in different areas of Brazil were selected. The subjects received a standardized questionnaire and were then contacted by phone for further clarification. The results demonstrated that the leadership is considered highly relevant by the subjects. It was possible also to detect facilitating and troublesome elements in the relationship between the leader and the virtual team. The major facilitating elements appointed by the virtual team were freedom of action, time flexibility and avoidance of administrative/bureaucratic procedures. On the bad side, lack of discipline and daily routine, inadequate working conditions and a feeling of social isolation were considered major handcups.(AU)